Band Conditioning Contractions Result in Greater Acute Performance Enhancement When Utilising Contrast Training in Elite Same Day Concurrently Trained Team Sport Athletes - Dean Ritchie; Justin Keogh; Peter Reaburn; Jon Bartlett (International Universities Strength and Conditioning Association, 2024)
Purpose: The aim of the current study was to assess the effect of altering conditioning contraction within contrast training on subsequent drop jump performance in the presence of same day concurrent training.  Methods: In a randomized crossover design, 8 professional Australian Football athletes completed same day skills/endurance training followed by resistance training utilizing different PAPE conditioning contractions (Strength, Band and Isometric). Conditioning contractions were performed for three sets of 3 repetitions; Strength (box squat, instructed to lift as heavy as possible), Band (band resisted, lower-force/ higher-velocity box squat) and Isometric (3 second maximal isometric quarter squat), with 3 DJ repetitions performed one minute following. Data were analyzed by fitting a mixed model (significance was set at P ≤ 0.05) to compare changes in DJ performance to respective baseline for each protocol with Dunnett's post hoc analysis applied.  Results: Compared to baseline, Band protocol resulted in the greatest increase in reactive strength index (RSI) for set 1 (P = 0.029) and 2 (P = 0.007), Stiffness for set 1 (P = 0.041) and 2 (P = 0.015), Mean Power for set 1 (P = 0.002) and 2 (P = 0.040), and Peak Power for set 1 (P = 0.002). Isometric increased RSI (P = 0.023) and Stiffness (P = 0.018) for set 1 only and Strength showed no improvement.  Conclusion: Practitioners working with athletes undertaking same day concurrent training should consider alternate modes of conditioning contraction such as Band conditioning contractions when prescribing contrast training to elicit a PAPE response.